Studi Eksegesis: “Apa Yang Dipersatukan Allah Tidak Boleh Diceraikan Manusia” Dalam Matius 19:6 - Pelealu, Nadia (Views : Jurnal Teologi dan Biblika, 2024)
Abstract: This research discusses what God has joined together and what man should not divorce in Matthew 19:6 (exegesis study). This command of God refers to the concept of marriage and divorce. In reality, many Christian couples face various problems that sometimes lead to divorce, and some to adultery. God clearly says that "they are no longer two, but one. Therefore, what God has joined together, let no man put asunder." Therefore, the purpose of writing this article is to give Christians a deeper understanding of God's intent and purpose in marriage. Marriage is seen as a sacred thing, done once in a lifetime. In this research, the author used a qualitative method and conducted a literature review as a source of material by looking at various books related to the topic, the Bible, journals and the internet. The approach taken was exegesis with word analysis and syntax analysis using the help of Bible Works 10.